Possible seizure suppression via deep brain stimulation of the thalamic ventralis oralis posterior nucleus - Wakerley, B; Schweder, P; Green, A; Aziz, T (2011)
Surgical treatment of intractable epilepsy with deep brain stimulation (DBS) has been shown to be of therapeutic benefit in some patients and with the recent publication of a randomised control study its use is likely to increase in the future. We describe a patient who developed a focal epileptic seizure within a few seconds of momentarily turning off the DBS stimulator in the nucleus ventralis oralis posterior, with which she was successfully treated for tremor. The seizure was the result of a newly diagnosed primary brain tumor. We suggest that the nucleus ventralis oralis posterior may be another thalamic target of DBS in epilepsy. © 2010 Elsevier Ltd. All rights reserved.